Experimental approach regarding investigation level of general physical training for tennis players aged 13 to 14 years - Panait, L.; Duta, D.; Negrea, V. (Science, Movement & Health, 2013)
Evolution sports performance in general and tennis in particular, has led to a great deal of domain experts to conclude that physical training has an important place in training athletes. Purpose was testing a target group and later to achieve implementation of new principles for achieving general physical training and developing models suscceptibile to be individualized for the main dimensions of the physicl demands with the introduction of novelty in the balance physical training. Methods.Tests were conducted on a group of eight advanced tennis players aged 13-14 years, engaged in the sport performance of 5 to 8 years, using a number of measurements, samples and tests used by the Romanian Tennis Federation. As results we found that scattering is very high in some tests, because the group is not homogeneous, coefficient of variability values indicating this, but we have many tests that indicate a scattering medium homogeneous or homogeneous group. Conclusion.Specific research effort playing tennis dimensions allows us to conclude that the most important physical qualities are those that are involved with the technical and tactical importance for increasing the efficiency of game players and become operational targets teaching or instructional objectives.